Inoculation of Soil with Plant Growth Promoting Bacteria Producing 1-Aminocyclopropane-1-Carboxylate Deaminase or Expression of the Corresponding acdS Gene in Transgenic Plants Increases Salinity Tolerance in Camelina sativa - Heydarian, Zohreh; Yu, Min; Gruber, Margaret; Glick, Bernard R.; Zhou, Rong; Hegedus, Dwayne D. (Frontiers in Microbiology, 2016)
Camelina sativa (camelina) is an oilseed crop touted for use on marginal lands; however, it is no more tolerant of soil salinity than traditional crops, such as canola. Plant growth-promoting bacteria (PGPB) that produce 1-aminocyclopropane-1-carboxylate deaminase (ACC deaminase) facilitate plant growth in the presence of abiotic stresses by reducing stress ethylene. Rhizospheric and endophytic PGPB and the corresponding acdS- mutants of the latter were examined for their ability to enhance tolerance to salt in camelina. Stimulation of growth and tolerance to salt was correlated with ACC deaminase production. Inoculation of soil with wild-type PGPB led to increased shoot length in the absence of salt, and increased seed production by approximately 30-50 percent under moderately saline conditions. The effect of ACC deaminase was further examined in transgenic camelina expressing a bacterial gene encoding ACC deaminase (acdS) under the regulation of the CaMV 35S promoter or the root-specific rolD promoter. Lines expressing acdS, in particular those using the rolD promoter, showed less decline in root length and weight, increased seed production, better seed quality and higher levels of seed oil production under salt stress. This study clearly demonstrates the potential benefit of using either PGPB that produce ACC deaminase or transgenic plants expressing the acdS gene under the control of a root-specific promoter to facilitate plant growth, seed production and seed quality on land that is not normally suitable for the majority of crops due to high salt content.